Direct cell extraction from fresh and stored soil samples: Impact on microbial viability and community compositions. (April 2021) - Ouyang, Yang; Chen, Danmei; Fu, Ying; Shi, Weiling; Provin, Tony; Han, Arum; van Shaik, Erin; Samuel, James E.; de Figueiredo, Paul; Zhou, Aifen; Zhou, Jizhong
Abstract: The direct extraction of viable microbes from soil samples is critical for the application of many single-cell related technologies. However, there are many aspects of extraction technologies that can impact the viability and diversity of extractable cells from fresh or stored soil samples. In this study, physical dispersion method, chemical dispersion method, and Nycodenz density gradient medium concentration were optimized with two sequential rounds of cell extraction from four soil samples having diverse physicochemical properties. Cell viability was quantified with fluorescence staining and flow cytometry. The viable microbial community compositions in soil extractable cells and soil samples were assessed after selective removal of DNA from dead cells. Among the four different extraction and purification methods, a protocol that included physical blending, Tween 20 treatment, and centrifugation with 80% Nycodenz, had the highest cell viability and yield. Repeated extraction increased the yield but reduced the cell viability. The over- or under-represented taxa in extractable cells might contribute to the bias of the extractable microbial communities. Using the optimized cell extraction procedure, the effect of soil storage conditions (4 °C, −80 °C, and air-drying) on yield, viability, and community composition of soil extractable cells were assessed. Cell viability decreased in all stored soil samples, but significant decreases in cell yield was only observed in air-dried soil samples. Microbial community compositions changed significantly in all stored soil samples, with the least changes were observed in soil stored at 4 °C, confirming that 4 °C short-term storage is suitable for highly efficient viable cell extraction. Taken together, the developed method offers great potential for advancing our analyses and understanding of soil microbial ecology and the role of individual microbes. Highlights: We optimized the procedure of soil cell extraction with two rounds of extraction. Blending + Tween 20 + 80% Nycodenz had the highest cell viability and yield. Repeated extraction increased the cell yield but reduced the cell viability. 4 °C short-term storage is suitable for efficient soil viable cell extraction.